Research on the saturated/unsaturated seepage laws of ionic rare earth ore under different leaching conditions - Guo, Zhongqun; Liu, Lingfeng; Zhou, Kefan; Wang, Xiaojun; Zhong, Wen (Frontiers in Earth Science, 2023)
The seepage law of the ionic rare earth leaching process plays an important role in the efficient development and utilization. The saturation permeation test of ionic rare earth under different leaching conditions was carried out using the variable head method, and the influence of type, concentration, and leaching path on the saturation permeability coefficient was revealed. The relationship between the water content and the matric suction of ionic rare earths under different leaching conditions was measured with the Geo-Experts pressure plate apparatus, and the soil-water characteristic curves under different leaching conditions were obtained. Based on the soil-water characteristic curve model, the unsaturated permeability coefficient function of ionic rare earths under different conditions was studied. The results show that the saturated-unsaturated permeability coefficients of ionic rare earths are pure water, 3% (NH4)2SO4, and 3% MgSO4, in descending order, when the type of leaching solution is different. For different concentrations of the leaching solution, when the concentration of (NH4)2SO4 increases from 2% to 5%, the saturated permeability coefficient first increases and then decreases. The matrix suction is an important factor affecting the unsaturated permeability coefficient when the ore body is unsaturated, and the unsaturated permeability coefficient decreases with the increase of the leaching solution concentration under the same matric suction. The seepage law is related to the leaching path, and the permeability coefficient increases when leaching at high concentrations followed by low concentrations, in reverse order, the permeability coefficient decreases. The research results can provide theoretical guidance for the design of injection parameters, and improve the theory of in-situ leaching.